Doctoral Dissertations in Economics Ninety-sixth Annual List (Journal of Economic Literature, 1999)
The list below specifies doctoral degrees conferred by U.S. and Canadian universities during academic year 1998–99. Lists of degree recipients and subject classifications are provided by the university.